2007
DOI: 10.1186/1477-7517-4-19
|View full text |Cite
|
Sign up to set email alerts
|

My first time: initiation into injecting drug use in Manipur and Nagaland, north-east India

Abstract: BackgroundThe north-east Indian states of Manipur and Nagaland are two of the six high HIV prevalence states in the country, and the main route of HIV transmission is injecting drug use. Understanding the pathways to injecting drug use can facilitate early intervention with HIV prevention programs. While several studies of initiation into injecting drug use have been conducted in developed countries, little is known about the situation in developing country settings. The aim of this study was to increase under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 19 publications
5
57
1
Order By: Relevance
“…Peer group pressure (54.59%), easy availability of drugs, curiosity and thrill-seeking behaviour (32.97%) were the most common reasons for initiation of the abuse. A similar set of reasons were reported from IDUs of north-east India by Kermode et al [11]. 40.54% (150/370) were addicted to using intra-venous (iv) injections of the drugs, whereas 13.51% (50/370) were using both iv and inhalation followed by 9.45% (35/370) of drugs by inhalation (smoking & snorting).…”
Section: Resultssupporting
confidence: 68%
“…Peer group pressure (54.59%), easy availability of drugs, curiosity and thrill-seeking behaviour (32.97%) were the most common reasons for initiation of the abuse. A similar set of reasons were reported from IDUs of north-east India by Kermode et al [11]. 40.54% (150/370) were addicted to using intra-venous (iv) injections of the drugs, whereas 13.51% (50/370) were using both iv and inhalation followed by 9.45% (35/370) of drugs by inhalation (smoking & snorting).…”
Section: Resultssupporting
confidence: 68%
“…This vulnerability may be explained by the inability of IDU to inject themselves, peer influence to try injection, variation in quality or availability of drugs, unemployment, borrowing needles/syringes from older IDU, not paying for first drug use as well as structural factors such as police harassment [10,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have described the importance of gender and gendered dynamics that characterise initiation into IDU. For example, some research has found that females and males are likely to be injected by males at initiation (Kermode et al, 2007). Although earlier research found that women tend to be first injected by a (male) sex partner (Crofts et al, 1996;Sherman et al, 2002), the relationship between female initiates and peer injectors has been found to differ across geographic areas (Tompkins et al, 2005), with an increasing number of reports highlighting women's role in initiating other women into IDU (Doherty et al, 2000;Bryant & Treloar, 2007).…”
Section: Peer Injectingmentioning
confidence: 96%